(untitled) - Korte, George (Australia, 2001)
Discover what a geographic information system (GIS) is, how it applies to a variety of professions, and the benefits of using GIS for a variety of applications. Praised through four highly successful editions, The GIS Book, 5th Edition now features hands-on exercises enabling readers to use free GIS software and data downloaded over the Internet to gain a first-hand understanding of the power of GIS technology today. New chapters on GIS data sources, data quality, plus managing and maintaining a GIS database have also been added to educate those new to GIS about one of the most important aspects of implementing any GIS project
Ứng dụng GIS trong quản lý thủy lợi
Keywords: Geographic information systems,Hệ thống thông tin địa lý